2020
DOI: 10.1016/j.lwt.2020.109605
|View full text |Cite
|
Sign up to set email alerts
|

Assessing acrylamide content in sterilized Californian-style black table olives using HPLC-MS-QQQ and a potentiometric electronic tongue

Abstract: The study aimed to evaluate the effects of olive cultivar (cvs. Manzanilla Cacereña and Hojiblanca) and the sterilization intensity/time-period (F 0 of 10-25 min at 121 ± 3°C) on the formation of acrylamide in table olives and brine. Olive cultivar and thermal sterilization had a significant impact on the amount of acrylamide produced (varying from 228 ± 94 to 286 ± 110 and 336 ± 126 to 373 ± 159 ng g −1 , for table olives and brine, respectively, determined by HPLC-MS-QQQ). Moreover, for both cultivars, linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…The samples were prepared by homogenizing the fine-grained olive to aqueous paste using deionized water, and the brine solutions were also diluted using deionized water to obtain the same proportions as olive. E-tongue membranes showed an increased response with a rising acrylamide content in olive oil and brine solutions, as reported by Martin-Vertedor et al [82]. In contrast, an electronic nose, or E-nose, is a sensor device with four gas sensor chips and metal oxide sensors and a data collection block that evaluates organic compounds responsible for the odor of cooked food.…”
Section: Electronic Tongue and Nosesupporting
confidence: 58%
“…The samples were prepared by homogenizing the fine-grained olive to aqueous paste using deionized water, and the brine solutions were also diluted using deionized water to obtain the same proportions as olive. E-tongue membranes showed an increased response with a rising acrylamide content in olive oil and brine solutions, as reported by Martin-Vertedor et al [82]. In contrast, an electronic nose, or E-nose, is a sensor device with four gas sensor chips and metal oxide sensors and a data collection block that evaluates organic compounds responsible for the odor of cooked food.…”
Section: Electronic Tongue and Nosesupporting
confidence: 58%
“…However, one study 2 has described the prediction of cooking defects produced by the application of different sterilization treatments to two varieties of oxidized black olives using an electronic tongue. These researchers also found that olive cultivar and sterilization treatment has a significant impact on the amount of cooking defect found due to its relationship with a toxic substance (acrylamide) in Californian‐style black olives 26 . Other researchers 27 have argued that electronic noses can be used as olfactory sensors to detect abnormal fermentation (such as zapateria , butyric , putrid , and musty ) in table olive defects in order to ensure their quality at industrial level.…”
Section: Resultsmentioning
confidence: 99%
“…These researchers also found that olive cultivar and sterilization treatment has a significant impact on the amount of cooking defect found due to its relationship with a toxic substance (acrylamide) in Californian-style black olives. 26 Other researchers 27 have argued that electronic noses can be used as olfactory sensors to detect abnormal fermentation (such as zapateria, butyric, putrid, and musty) in table olive defects in order to ensure their quality at industrial level. In this way these results indicated the feasibility of these devices as rapid analytical tools for monitoring the elaboration process of table olives.…”
Section: Quantification Of Sensory Parameters Using An E-nosementioning
confidence: 99%
“…Regarding the volatile compounds, Californian-style black olives have a characteristic odour of a cooked sensory note [ 15 , 23 , 41 ] that is mainly provoked by the thermal treatment that was used to stabilize these types of olives. Following IOC regulations, the results obtained by these researchers can classify table olives that have been submitted to different sterilization treatments into different sensory categories after considering the predominantly perceived defect (PPD) and intensity attributes.…”
Section: Discussionmentioning
confidence: 99%
“…In the NMR spectrum, acrylamide is not directly quantifiable, so these researchers established a correlation between the reference value and the corresponding NMR spectrum using a partial least squares (PLS) regression [ 44 ]. Furthermore, Martín-Vertedor et al [ 41 ] established a direct linear model between acrylamide content and potentiometric electronic tongue to monitor the content of this toxic substance in Californian-style black olive. Therefore, the use of electronic devices for acrylamide detection is of interest since industries will be able to determine the content of this toxic substance quickly, efficiently, and reliably.…”
Section: Discussionmentioning
confidence: 99%